2020
DOI: 10.3390/jrfm13120331
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Crowdfunding Campaign Success: The Influence of First Impressions on Accuracy and Positivity

Abstract: Crowdfunding has quickly gained popularity in recent years, providing an additional way for entrepreneurial individuals and organizations (creators) to attract funds for their projects. Scholars have been interested in predicting the success of crowdfunding campaigns, by relating campaign characteristics to the actual success of these campaigns. We take one step back by studying the cognitive processes of the crowd. This paper uses an experimental approach to establish whether participants’ predictions on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…in their research, Hossain andOparaocha (2017), andFanea-Ivanovici andSiemionek-Ruskań (2019) observed that the use of the internet, marketing channels, the ability to test new innovative and creative ideas, and the direct interaction with the customers are few elements differentiating crowdfunding from other traditional fundraising campaigns. Additionally, crowdfunding platforms allow startups to entice investors by advertising their new or innovative ideas through the internet (Schraven et al, 2020)providing an additional way for entrepreneurial individuals and organizations (creators. using the internet also sets aside the crowdfunding campaigns from the traditional fundraising campaigns through generating a wide range of audiences (Fanea-ivanovici &Siemionek-Ruskań, 2019 andtafesse, 2021).…”
Section: Concept Of Crowdfundingmentioning
confidence: 99%
“…in their research, Hossain andOparaocha (2017), andFanea-Ivanovici andSiemionek-Ruskań (2019) observed that the use of the internet, marketing channels, the ability to test new innovative and creative ideas, and the direct interaction with the customers are few elements differentiating crowdfunding from other traditional fundraising campaigns. Additionally, crowdfunding platforms allow startups to entice investors by advertising their new or innovative ideas through the internet (Schraven et al, 2020)providing an additional way for entrepreneurial individuals and organizations (creators. using the internet also sets aside the crowdfunding campaigns from the traditional fundraising campaigns through generating a wide range of audiences (Fanea-ivanovici &Siemionek-Ruskań, 2019 andtafesse, 2021).…”
Section: Concept Of Crowdfundingmentioning
confidence: 99%
“…The results of this study can be viewed as a supplement to the research presented by Usman et al [61] concerning the problem of information asymmetry in decision-making processes in crowdfunding. As already mentioned, the lack of "fairly" available information is particularly noticeable here, and when such a situation occurs, decisions can be highly influenced by emotions or the first impressions, as discussed by Schraven et al [64]. The analysis and classification of crowdfunding attributes presented in this paper provides a large amount of information that may constitute the basis for more rational decisions, especially taking into account that the research results are presented in various crosssections, and the obtained category classes of projects or attributes make it possible to capture their similarity and the strength of correlation.…”
Section: Discussionmentioning
confidence: 76%
“…A clearly behavioral approach was adopted in the article by Schraven et al [64], called "Predictions of Crowdfunding Campaign Success: The Influence of First Impressions on Accuracy and Positivity". Venturelli et al [65] also took on a behavioral perspective when investigating the relationship between gender and ethnic origin of the person submitting the project and its backers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also established that the gender of campaigners influenced the generation of funding on crowdfunding platforms. Schraven et al [13] evaluated the campaign success from the perspective of cognitive biases of the participants in w.r.t duration of assessment of positivity about the Kickstarter projects. Shane and Cable [14] and Zheng et al [15] have showed that the influence of an individual's social media connections in raising funds successfully is significant.…”
Section: Related Workmentioning
confidence: 99%